ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS TULIS SISWA SMP DITINJAU DARI KECERDASAN INTERPERSONAL - Arezqi Tunggal Asmana (LPPM STKIP PGRI Sidoarjo, 2022)
This study aims to describe the written mathematical communication skills of junior high school students in terms of high, medium and low interpersonal intelligence. This research is a descriptive study with a qualitative approach. The subjects in this study were 6 class VIII-A students of SMP NU Simo in the 2019/2020 school year. The determination of the subject is based on the results of the interpersonal intelligence test. The question instrument given to the research subjects was a description test consisting of 3 items. The data used are the results of tests and interviews. The indicators of written mathematical communication skills in this study are (1) expressing mathematical ideas by writing down information on the problem about what is known and asked, (2) expressing ideas, daily situations and mathematical relations by describing shapes and description of the appropriate size problems, (3) understand and interpret mathematical ideas by writing the concept of formulas, steps and calculation of problem solving, (4) evaluating mathematical ideas by writing appropriate conclusions at the end of problem solving, and (5) using mathematical symbols in write down known information and process problem solving. Based on the data analysis that has been carried out, the results of this study indicate that: (1) junior high school students' written mathematical communication skills in terms of high interpersonal intelligence are able to meet 5 indicators of written mathematical communication skills, namely indicators 1, 2, 3, 4, and 5; (2) the written mathematical communication skills of junior high school students in terms of moderate interpersonal intelligence are able to meet 4 indicators of written mathematical communication skills, namely indicators 1, 3, 4, and 5; (3) written mathematical communication skills of junior high school students in terms of low interpersonal intelligence are able to meet 3 indicators of written mathematical communication skills, namely indicators 1, 3, and 4.